2018
DOI: 10.1177/2333794x17750271
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Regimens and Gastrointestinal Tolerance: A Multicenter, Prospective, Observational Cohort Study in China

Abstract: To study feeding tolerance in infants fed formula with increased sn-2 palmitate and oligofructose (sn-2+OF) in a real-world setting, healthy Chinese infants were enrolled in this 48-day observational study on their current feeding regimens: exclusively breastfed (BF; n = 147), exclusively sn-2+OF formula-fed (FF; n = 150), or mixed-fed with breast milk and sn-2+OF formula (MF; n = 163). Throughout the study, incidence (90% confidence interval) of hard stools was ≤2.1% (0.0-5.3) in FF and 0.8% (0.0-3.5) in MF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(77 reference statements)
2
4
0
Order By: Relevance
“…The average baseline IGSQ sum score of 36 in this study confirms findings from previous studies that regurgitation is frequently associated with other GI symptoms (11,12). IGSQ sum scores improved significantly within 1 week and after 4 weeks, scores were comparable to values reported in healthy term born infants without specific GI issues (23,27–31).…”
Section: Discussionsupporting
confidence: 88%
“…The average baseline IGSQ sum score of 36 in this study confirms findings from previous studies that regurgitation is frequently associated with other GI symptoms (11,12). IGSQ sum scores improved significantly within 1 week and after 4 weeks, scores were comparable to values reported in healthy term born infants without specific GI issues (23,27–31).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, infants who switched to a formula containing L. reuteri and 2′fucosyllactose improved their IGSQ composite score from above 30 to 22.1 after receiving the L. reuteri -containing formula for 3 weeks [ 19 ]. Other studies conducted in the US and in China using the IGSQ to assess GI tolerance of formulas with optional ingredients reported lower composite scores [ 20 , 21 ]. Differences among studies might be explained by different effects of the various optional formula ingredients that were studied.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an interventional real-world evidence study in Spain found no difference in IGSQ scores after 8 weeks among infants receiving a formula with 2’fucosyllactose and lacto-n-neotetraose, infants receiving a mixture of formula and breastmilk, and exclusive BFI (mean IGSQ scores 20.7, 20.4, and 19.9, respectively) [ 18 ]. Another real-world study in China had similar IGSQ scores among infants receiving a formula with added sn-2 palmitate and oligofructose (sn-2 + OF), a mixture of sn-2 + OF formula and breastmilk, and breastmilk alone (mean IGSQ scores after 18 days were 17.5, 18.2, and 16.3, respectively) [ 19 ]. Collectively, these results, including the present study, demonstrate good GI tolerance for pre- and/or probiotic supplemented formulas comparable to that in BFI.…”
Section: Discussionmentioning
confidence: 99%